2018
DOI: 10.1111/bcp.13792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of prescription opioid analgesic use in Australia

Abstract: Aims The aims of the current study were to determine the prevalence and incidence of prescription opioid analgesic use in Australia and compare the characteristics of people with and without cancer initiating prescription opioid analgesics. Methods A retrospective population‐based study was conducted using the random 10% sample of adults who were dispensed prescription opioid analgesics in Australia between July 2013 and June 2017 through the Pharmaceutical Benefits Scheme. Poisson regression was used to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 34 publications
0
117
0
Order By: Relevance
“…Our results have clinical practice and policy implications because high doses have been associated with substantial morbidity and mortality, including, falls, fractures, hospitalization, motor vehicle accidents, opioid‐related overdose and death . A recent Australian study reported that 1.9 million people initiate opioids each year . By extrapolation, approximately 26 600 people who initiate opioids escalate to high doses over 12 months.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Our results have clinical practice and policy implications because high doses have been associated with substantial morbidity and mortality, including, falls, fractures, hospitalization, motor vehicle accidents, opioid‐related overdose and death . A recent Australian study reported that 1.9 million people initiate opioids each year . By extrapolation, approximately 26 600 people who initiate opioids escalate to high doses over 12 months.…”
Section: Discussionmentioning
confidence: 68%
“…Previous Australian research has indicated that the RxRisk‐V tool identifies fewer people with cancer compared to the Charlson's Comorbidity Index (43.2 versus 67.2%), which is widely used and considered a ‘gold standard’ approach to assess disease burden . For this reason we used a more comprehensive medication‐based indicator of cancer treatment that included other anti‐neoplastic therapies such as hormonal cancer therapies . Cancer treatment history was used as a predictor because cancer‐related pain could influence the rate of opioid transitions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations